Indices of psychic status in the people with regular and irregular rhythm of the intestine - K. A. Shemerovsky (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The level of neuropsychic adaptation and regularity of the circadian rhythm of the evacuatory function of the intestine were investigated in the working people. The people were divided - according to the psychic state - into 4 main groups: I - practically healthy people - 22 %, prenosologic condition - 22 %, III - pre-pathologic condition - 27 %, IV - pathology condition - 29 %. The people with the irregular rhythm of the intestine demonstrate worsening of the psychic state from 2 to 6 times more frequently than in the people with a regular rhythm of the intestine.